Nixtamalization Effects on the Contents of Phytic Acid in the Varieties of Maize and the Bioavailability of Iron in Nixtamalized Maize to Young Pigs - Rong, L.I.; Kang-Ning, Wang (Pakistan Journal of Nutrition, 2009)
The present study was conducted to investigate the effect of nixtamalization process on the phytic acid loss of maize and the subsequent influence on iron bioavailability of the iron-deficient piglets. Two experiments were conducted to achieve the objective: in the first step, three types of maize varying in phytic acid contents were processed by five lime concentrations treatment (0, 0.6, 1.2, 1.8 and 2.4%), four cooking duration (0, 45, 60 and 75 min) and thereafter soaking for five periods (0, 2, 4, 6 and 8 h) to optimize the best nixtamalization process parameter based on the maximum loss of phytic acid. In the second study, weaning piglets suffered iron-deficient were fed two diets: either lime-cooked maize produced by optimal parameter (NTM) or non-nixtamalized maize as control (CON), to examine the effects of the nixtamalization on the iron bioavailability, iron status and growth performance. The results showed that: (1)The greatest phytic acid loss of three types of maize and their processing parameters (lime concentration, cooking duration and steeping duration) were 17.4% (1.2%, 75 min and 4 h), 14.9% (1.8%, 75 min and 4 h) and 27.5% (1.8%, 75 min and 4 h), respectively. (2) The hemoglobin concentration (Hb), Packed Cell Volume (PCV), Red Blood Cell count (RBC) and Hemoglobin-Fe (Hb-Fe) content were improved in the NTM piglets compared with CON piglets (p